1996
DOI: 10.1097/00004691-199607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Past and Future of Computer-Assisted Sleep Analysis and Drowsiness Assessment

Abstract: The development of computerized sleep analysis has been very much technology-driven by both mathematical tools and available hardware but, additionally and unfortunately, by the almost-30-year-old standard used for manual sleep stage scoring of paper recordings. There are no technical restrictions in terms of computing power, storage space, and costs anymore. However, the standards of visual sleep stage scoring have proven insufficient and ambiguous, and their utilization evidently provides misleading and erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 79 publications
0
50
0
Order By: Relevance
“…Most previous efforts on automated staging [4], [5], [14], [28] have shown the separation of SWS into stages 3 and 4 to be generally poor. When these two stages are pooled, however, the overall performance improves drastically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous efforts on automated staging [4], [5], [14], [28] have shown the separation of SWS into stages 3 and 4 to be generally poor. When these two stages are pooled, however, the overall performance improves drastically.…”
Section: Discussionmentioning
confidence: 99%
“…In all likelihood, the computer detection/separation of SWS into stages 3 and 4 is more consistent than manual scoring since it is based on an objective measurement. As suggested in [28], computer scoring of SWS should overrule manual scoring and not vice versa. It is our feeling that the visual distinction between stages 3 and 4 is bound to lead to less consistent performance as compared with an objective measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millán et al [31] present a neural classifier to recognize mental tasks and get about 70% correct recognition. Researchers have found that fluctuations in wakefulness can be examined with EEG measurement from active subjects with eyes open and engaged in their usual awake activities [4], [20]. In these situations, intrusions of alpha and theta activity into the beta activity of active wakefulness have been interpreted as ensuing sleepiness.…”
mentioning
confidence: 99%
“…Visual analysis of the recordings requires a considerable amount of effort. Therefore, several attempts have been made to automate this process [4].…”
Section: Introductionmentioning
confidence: 99%